Ambipolar transport in tin dioxide thin film transistors promoted by PCBM fullerene - Boratto, Miguel H. [UNESP]; Scalvi, Luis V. A. [UNESP]; Goncharova, Lyudmila V.; Fanchini, Giovanni (Springer Nature, 2018)
In this article, the effect of phenyl-C61-butyric acid methyl ester (PCBM) layer on the electrical performance of field-effect transistors (FETs) based on antimony-doped tin dioxide (Sb:SnO2) is reported. PCBM is a soluble variety of fullerene, n-type organic semiconductor, known to promote the p-type doping of semiconducting materials such as diamond and graphene, via charge transfer. Sb:SnO2 is an emerging low-cost transparent oxide semiconductor material that exhibits strong unipolar behavior (n-type). Ambipolar character in tin dioxide normally is not observed, however in this study we find that the deposition of PCBM on top of Sb:SnO2 promotes ambipolar behavior in Sb:SnO2 FETs. At negative gate bias (VG < 0) PCBM traps free electrons from the conduction band of SnO2 and from Sb donors, thus downshifting the Sb:SnO2 Fermi level (EF), leading to a strong injection of holes in the valence band of Sb:SnO2. The p-type carrier concentration increases up to 8.6 × 1011 cm−2. Our results suggest that PCBM deposition decreases the current in the accumulation mode of electrons due to electron mobility decrease at VG > 0, and enhances the current in inversion mode. Besides, PCBM deposition also results in an increase of hole mobility at VG < 0.